Antiglare film, polarizing plate and display device

A laminate with controlled surface irregularities in anti-glare films for high-resolution displays addresses sparkling issues, ensuring excellent anti-glare and optical properties while maintaining image clarity.

JP7616752B2Active Publication Date: 2025-01-17XINMEI HOLDINGS (HONG KONG) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022548188
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-10
Filing Date
2021-03-02
Publication Date
2025-01-17
Estimated Expiration
2041-03-02

AI Technical Summary

Technical Problem

Anti-glare films applied to displays with high resolution and pixel density, such as OLEDs and micro-LEDs, cause sparkling phenomena and reduce image brightness due to surface irregularities that act as refracting lenses.

Method used

A laminate with a light-transmitting base material and a hard coating layer containing a binder resin and dispersed organic and inorganic particles, with specific haze and peak area ratios, transmission diffusion distribution, and specular reflection intensity within defined ranges, to control surface irregularities and prevent sparkling.

Benefits of technology

The laminate achieves excellent anti-glare properties with high light transmittance, scratch resistance, and stain resistance, preventing sparkling and maintaining image clarity on high-resolution displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616752000001
    Figure 0007616752000001
  • Figure 0007616752000002
    Figure 0007616752000002
Patent Text Reader

Abstract

The present invention relates to an antiglare film that includes a laminate including a light-transmitting substrate and a hard coating layer that includes a binder resin and organic particles and inorganic particles dispersed in the binder resin, and that satisfies specific ranges for the difference between overall haze and internal haze, the peak area ratio of the IR spectrum, and the transmission diffusion distribution, as well as a polarizing plate and a display device that include the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [Cross-reference to related application(s)] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0027918 filed on March 5, 2020, and Korean Patent Application No. 10-2020-0029751 filed on March 10, 2020, and all contents disclosed in the documents of said Korean patent application are incorporated herein by reference.

[0002] The present invention relates to an antiglare film, a polarizing plate, and a display device including the same. [Background technology]

[0003] When exposed to external light such as natural light, flat panel displays (FPDs) have the problem that the surface reflected light can cause eye fatigue or headaches, and the image created inside the display cannot be recognized clearly. To solve these problems, anti-glare films are used to scatter external light on the surface by forming unevenness on the display surface, or to induce internal scattering by using the refractive index between the resin and particles that form the coating film.

[0004] However, when the anti-glare film is applied to displays such as OLED, mini LED, and micro LED, which require high resolution and pixel density, the surface irregularities formed on the surface of the anti-glare film act as lenses that greatly refract light emitted from pixels, causing a sparkling phenomenon and distorting the image expression, resulting in a decrease in image brightness.

[0005] Therefore, there is a need to develop technology to prevent sparkling and improve image brightness by controlling the size and cohesion of the surface irregularities of anti-glare films applied to displays such as OLED, mini LED, and micro LED, which require high resolution and high pixel density. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention aims to provide an antiglare film that exhibits excellent antiglare properties while preventing the sparkling phenomenon, and exhibits excellent optical properties such as high light transmittance while also exhibiting excellent physical properties such as scratch resistance, high strength and stain resistance.

[0007] Another object of the present invention is to provide a polarizing plate including the antiglare film.

[0008] Another object of the present invention is to provide a display device that includes the antiglare film and provides high screen clarity. [Means for solving the problem]

[0009] As used herein, the present invention includes a laminate including a light-transmitting substrate; and a hard coating layer including a binder resin and organic particles and inorganic particles dispersed in the binder resin; The laminate has a difference (Ha-Hi) between the overall haze (Ha) and the internal haze (Hi) of 5 to 15%, The IR spectrum of the laminate shows a peak at 1690 cm -1 ~1745cm -1 The peak area between the regions (I A ) for 1500 cm -1 ~1570cm -1 The peak area between the regions (I B ) ratio (I B / I A ) is 0.1 to 0.6, An antiglare film may be provided in which the transmittance diffusion distribution of the laminate according to the following formula 1 is more than 1% and less than 10%. [Formula 1] Transmission diffusion distribution = (B / A) x 100 A is the transmission intensity measured by irradiating light in the normal direction of the light-transmitting substrate and then transmitting the light in the normal direction of the hard coating layer, B is the transmitted diffuse intensity measured by irradiating the light in the normal direction of the light-transmitting substrate and then measuring the light transmitted at +1° or −1° with respect to the normal of the hard coating layer.

[0010] Further, the present specification provides a polarizing plate including the antiglare film.

[0011] Also provided herein is a display device comprising the antiglare film.

[0012] Hereinafter, an antiglare film according to a specific embodiment of the present invention, a polarizing plate including the same, and a display device will be described in more detail.

[0013] As used herein, (meth)acrylate is intended to include both acrylate and methacrylate.

[0014] In addition, in this specification, weight average molecular weight (Mw) means a molecular weight (unit: Da (Dalton)) in terms of polystyrene measured by gel permeation chromatography (GPC). In the process of measuring the weight average molecular weight in terms of polystyrene measured by the GPC method, a commonly known analyzer, a detector such as a refractive index detector, and an analytical column can be used, and commonly applied temperature conditions, solvents, and flow rates can be applied. Specific examples of the measurement conditions include using a Polymer Laboratories PLgel MIX-B 300 mm long column and a Waters PL-GPC220 instrument, the evaluation temperature is 160° C., 1,2,4-trichlorobenzene is used as a solvent, the flow rate is 1 mL / min, the sample is prepared to a concentration of 10 mg / 10 mL, and then supplied in an amount of 200 μL, and the Mw value can be obtained using a calibration curve formed using polystyrene standards. Nine types of polystyrene standards with molecular weights of 2,000 / 10,000 / 30,000 / 70,000 / 200,000 / 700,000 / 2,000,000 / 4,000,000 / 10,000,000 were used.

[0015] According to one embodiment of the present invention, a laminate including a light-transmitting substrate; and a hard coating layer including a binder resin and organic particles and inorganic particles dispersed in the binder resin; wherein the laminate has a difference (Ha-Hi) between an overall haze (Ha) and an internal haze (Hi) of 5 to 15%. -1 ~1745cm -1 The peak area between the regions (I A ) for 1500 cm -1 ~1570cm -1 The peak area between the regions (I B ) ratio (I B / I A ) is 0.1 to 0.6, and the transmission diffusion distribution of the laminate according to formula 1 is more than 1% and less than 10%.

[0016] The present inventors have provided a laminate including a light-transmitting substrate, and a hard coating layer including a binder resin, organic particles, and inorganic particles, the laminate having a difference between the overall haze (Ha) and the internal haze (Hi) of 5 to 15%, and the peak area ratio (I B / I A ) is 0.1 to 0.6 and the transmission diffusion distribution is more than 1% but less than 10%, excellent antiglare properties are exhibited and sparkling does not occur even when the film is applied to a display panel requiring high resolution. This has been confirmed, and the present invention has been completed.

[0017] Specifically, the above-mentioned specific numerical ranges of the difference between the total haze (Ha) and the internal haze (Hi), the peak area ratio, and the transmission diffusion distribution of the antiglare film may be due to the binder resin composition of the hard coating layer, the diameters of the organic particles and the inorganic particles dispersed in the binder resin, or the weight ratio of the organic particles and the inorganic particles.

[0018] The laminate contained in the antiglare film may have a difference (Ha-Hi) between the total haze (Ha) and the internal haze (Hi) of 5 to 15%, 7 to 14%, or 9 to 13%. If the difference between the total haze and the internal haze is less than 5%, the antiglare effect due to external unevenness may decrease, and if it exceeds 15%, sparkling may become severe and image clarity may decrease.

[0019] The laminate may have an overall haze (Ha) of 20% to 50%, 25% to 45%, or 30% to 40%. If the overall haze is too small, a sparkling phenomenon may occur or anti-glare properties may not be exhibited, and if the overall haze is too large, the opacity of the film may increase and the light-dark ratio may decrease.

[0020] In addition, the laminate may have an internal haze of 10% to 40%, 15% to 35%, or 20% to 30%. If the internal haze is too small, a sparkling phenomenon may occur, and if the internal haze is too large, the opacity of the film may increase, resulting in a decrease in the light-dark ratio.

[0021] The IR spectrum of the laminate contained in the antiglare film shows a peak at 1690 cm -1 ~1745cm -1 The peak area between the regions (I A ) for 1500 cm -1 ~1570cm -1 The peak area between the regions (I B The ratio (IB / IA) of the peak areas may be 0.10 to 0.60, 0.20 to 0.58, or 0.30 to 0.55. B / I A If the ratio is less than 0.10, the unevenness may not be uniformly formed in the shape of protrusions, and sparkling may occur. If the ratio exceeds 0.60, the unevenness due to particle aggregation may decrease, and the anti-glare effect may decrease.

[0022] The IR spectrum may be measured for the hard coating layer of the antiglare film using an IR spectrum measuring device, Cary660 (Agilent), under the conditions of a temperature of 20 to 25° C. and a humidity of 40 to 50%.

[0023] The laminate contained in the antiglare film may have a transmission diffusion distribution of more than 1% and less than 10%, 3% to 8%, or 4% to 7% according to the following formula 1. If the transmission diffusion distribution is 1% or less, there is a problem that the antiglare effect is reduced, and if it is 10% or more, there is a problem that sparkling occurs. [Formula 1] Transmission diffusion distribution = (B / A) x 100 A is the transmission intensity measured by irradiating light in the normal direction of the light-transmitting substrate and then transmitting the light in the normal direction of the hard coating layer, B is the transmitted diffuse intensity measured by irradiating the light in the normal direction of the light-transmitting substrate and then measuring the light transmitted at +1° or −1° with respect to the normal of the hard coating layer.

[0024] Specifically, in the transmission diffusion distribution, the transmission intensity (A) and the transmission diffusion intensity (B) can be classified into the transmission intensity (A) and the transmission diffusion intensity (B) according to the measurement angle of the transmitted light when the irradiated light is transmitted through the hard coating layer after irradiating the light in the normal direction of the light-transmitting substrate. Specifically, the intensity of the transmitted light measured in the normal direction of the hard coating layer is the transmission intensity (A), which can be defined as the regular transmission intensity. In addition, the intensity of the transmitted light measured at +1° or -1° based on the normal of the hard coating layer is the transmission diffusion intensity (B).

[0025] In this case, when measuring the transmission intensity (A) and the transmission diffusion intensity (B), the intensity of the light irradiated in the normal direction of the light-transmitting substrate is constant. Specifically, when the intensity of the light irradiated in the normal direction of the light-transmitting substrate is 100, the transmission intensity (A) may be 10 to 60, 20 to 50, or 25 to 45, and the transmission diffusion intensity (B) may be 0.1 to 6, 0.2 to 5, or 0.25 to 4.5.

[0026] The laminate contained in the antiglare film may have a specular reflection intensity ratio of more than 1% and less than 10%, 3% to 8%, or 4% to 7% as shown in the following formula 2. If the specular reflection intensity ratio is 1% or less, sparkling may occur or image clarity may decrease, and if it is 10% or more, there is a problem that the antiglare effect decreases. [Formula 2] Specular reflection intensity ratio=(C / D)×100 In the above formula 2, C is the reflection intensity measured at an incidence angle of 45°, which corresponds to the specular reflection, after irradiating the hard coating layer with light at an incidence angle of 45°; D is the reflection intensity measured at an incidence angle of 45°, which corresponds to regular reflection, after irradiating the light-transmitting substrate with light at an incidence angle of 45°.

[0027] The regular reflection intensity ratio in the above formula 2 is calculated as a percentage of the reflection intensity (C) measured for the hard coating layer relative to the reflection intensity (D) measured for the light-transmitting substrate.

[0028] When light is irradiated at an angle of 45° from the normal to the surface of the hard coating layer or light-transmitting substrate to be measured, some of the light is diffused at 45°, which corresponds to the specular reflection of the incident angle, and the light intensity measured at 45°, which is the specular reflection direction of the incident angle, is defined as reflection intensity (C) or reflection intensity (D) depending on the object to be measured. In addition, to suppress backside reflection and match the conditions during actual use, a non-light-transmitting substrate is attached to the backside of the object to be measured.

[0029] The non-transparent substrate is a substrate that has a light transmittance of almost 0% and does not transmit any light such as visible light, and may be, for example, a black acrylic plate, black horse manure paper, or a film coated with a black adhesive. The film coated with a black adhesive may be, for example, a polyethylene terephthalate film coated with a black adhesive.

[0030] More specifically, in order to measure the reflection intensity (C), first, the non-transparent substrate, which is flat and free of unevenness or warping, can be attached to one side of the light-transmitting substrate so as to face the hard coating layer. Then, light is incident on the surface of the hard coating layer at an angle of 45° from the normal line of the surface, and the reflection intensity (C) can be measured at an incident angle of 45°, which corresponds to regular reflection. The reflection intensity (C) can be 1000 to 6000, 1500 to 5000, or 2000 to 4000.

[0031] In order to measure the reflection intensity (D), only a light-transmitting substrate without a hard coating layer is prepared, and a non-light-transmitting substrate is attached to one side of the light-transmitting substrate. Then, a light beam is incident on the one side of the light-transmitting substrate to which the non-light-transmitting substrate is not attached at an angle of 45° from the normal line of the surface, and the reflection intensity (D) can be measured at 45°, which corresponds to the regular reflection of the incident angle. The reflection intensity (D) can be 50,000 to 70,000, 52,000 to 68,000, or 55,000 to 65,000.

[0032] The antiglare film may include a hard coating layer, and the hard coating layer may include a binder resin and organic particles and inorganic particles dispersed in the binder resin.

[0033] The binder resin may include a polyfunctional (meth)acrylate monomer and a urethane (meth)acrylate oligomer.

[0034] The polyfunctional (meth)acrylate monomer may contain 2 or more, 3 to 10, or 4 to 9 (meth)acrylate functional groups and have a weight average molecular weight of 1,500 g / mol or less, 1,000 g / mol or less.

[0035] Such a polyfunctional (meth)acrylate monomer may be, but is not limited to, at least one selected from the group consisting of pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, tolylene diisocyanate, xylene diisocyanate, hexamethylene diisocyanate, trimethylolpropane tri(meth)acrylate, trimethylolpropane polyethoxy tri(meth)acrylate, trimethylolpropane trimethacrylate, ethylene glycol dimethacrylate, butanediol dimethacrylate, hexaethyl methacrylate, and butyl methacrylate.

[0036] The urethane (meth)acrylate oligomer may contain 2 or more, 3 to 20, or 4 to 15 (meth)acrylate functional groups and have a weight average molecular weight of 700 g / mol to 10,000 g / mol, or 1,000 g / mol to 8,000 g / mol, or 1,500 g / mol to 5,000 g / mol.

[0037] In addition, the urethane (meth)acrylate oligomer may have an equivalent weight of the (meth)acrylate functional group of 100 to 500 g / mol, 150 g / mol to 450 g / mol, or 200 g / mol to 400 g / mol. The equivalent weight of such functional group is the value obtained by dividing the molecular weight of the polysiloxane by the number of functional groups, and can be analyzed by H-NMR or chemical titration.

[0038] The urethane (meth)acrylate oligomer may be, for example, but is not limited to, a urethane modified acrylate oligomer, an epoxy acrylate oligomer, an ether acrylate oligomer, a resinous acrylate oligomer, or a mixture of two or more of these.

[0039] The weight ratio of the polyfunctional (meth)acrylate monomer and the urethane (meth)acrylate oligomer contained in the hard coating layer may be 3:7 to 7:3, 4:6 to 7:3, 5:5 to 7:3, or 6:4 to 7:3. If the content of the polyfunctional (meth)acrylate monomer is too high compared to the urethane (meth)acrylate oligomer, excessively large unevenness may be formed in the hard coating layer, the transmission diffusion distribution may be 10% or more, sparkling may occur, and image clarity may be reduced. On the other hand, if the content of the polyfunctional (meth)acrylate monomer is too low compared to the urethane (meth)acrylate oligomer, almost no unevenness may be formed in the hard coating layer, the external haze may be low, and the transmission diffusion distribution may be 1% or less, resulting in reduced anti-glare effect.

[0040] The hard coating layer included in the anti-glare film according to the embodiment includes a binder resin including a multifunctional (meth)acrylate monomer and a urethane (meth)acrylate oligomer in a weight ratio of 3:7 to 7:3, and may include organic particles having a particle size of 1 μm to 10 μm and inorganic particles having a particle size of 1 nm to 500 nm. As a result, the anti-glare film satisfies the above-mentioned ranges in the difference between the total haze (Ha) and the internal haze (Hi), the peak area ratio, and the transmission diffusion distribution, thereby improving the anti-glare properties, and in particular, the sparkling phenomenon can be prevented even when applied to a display panel that requires high resolution.

[0041] The organic particles may have a particle size of 1 μm to 10 μm, 2 μm to 9 μm, 3.5 μm to 8 μm, or 3.5 μm to 7 μm. If the particle size of the organic particles contained in the hard coating layer is too small, it is difficult to achieve anti-glare properties, and if the particle size is too large, sparkling may occur.

[0042] The organic particles may have a refractive index of 1.500 to 1.600, 1.520 to 1.600, or 1.540 to 1.595 based on a wavelength of 500 to 600 nm. By including organic particles having a high refractive index in the hard coating layer as described above, it is possible to prevent sparkling defects and unevenness occurring inside the panel from being visually recognized while exhibiting excellent antiglare properties.

[0043] The refractive index may be measured at a wavelength of 500 nm to 600 nm using a SPA-4000 prism coupler from Sairon Technology Co., Ltd.

[0044] The type of the inorganic particles is not limited thereto, but may be, for example, one selected from polystyrene, polymethyl methacrylate, polymethyl acrylate, polyacrylate, polyacrylate-co-styrene, polymethyl acrylate-co-styrene, polymethyl methacrylate-co-styrene, polycarbonate, polyvinyl chloride, polybutylene terephthalate, polyethylene terephthalate, polyamides, polyimides, polysulfone, polyphenylene oxide, polyacetal, epoxy resin, phenolic resin, silicone resin, melamine resin, benzoguanamine, polydivinylbenzene, polydivinylbenzene-co-styrene, polydivinylbenzene-co-acrylate, polydiallyl phthalate, and triallyl isocyanurate copolymers, or a copolymer of two or more of these may be used.

[0045] The organic particles may be 5 to 30 parts by weight, 7 to 25 parts by weight, or 10 to 20 parts by weight based on 100 parts by weight of the binder resin. If the content of the organic particles is too low, it is difficult to achieve antiglare properties, and if the content of the organic particles is too high, excessive sparkling may occur.

[0046] The inorganic particles may have a size of 1 nm to 500 nm, 5 nm to 450 nm, 10 nm to 400 nm, or 15 nm to 350 nm. If the particle size of the inorganic particles contained in the hard coating layer is too small, it is difficult to achieve anti-glare properties, and if the particle size is too large, sparkling may occur.

[0047] The type of the inorganic particles is not limited thereto, but may be, for example, one or more selected from the group consisting of silica, titanium dioxide, indium oxide, tin oxide, zirconium oxide, zinc oxide, and polysilsesquioxane particles. The polysilsesquioxane may be a cage-structured silsesquioxane particle.

[0048] The inorganic particles may be contained in an amount of 5 to 30 parts by weight, 10 to 27 parts by weight, or 15 to 22 parts by weight, based on 100 parts by weight of the binder resin. If the content of the inorganic particles is too low, it is difficult to achieve antiglare properties, and if the content of the inorganic particles is too high, excessive sparkling may occur.

[0049] The weight ratio of the organic particles to the inorganic particles may be 1:0.2 to 1.5, 1:0.4 to 1.2, or 1:0.5 to 1.0. If the content of the inorganic particles is too low compared to the organic particles, anti-glare properties may be reduced, and if the content of the inorganic particles is too high, sparkling may occur, reducing image clarity.

[0050] The organic particles and inorganic particles may have a particle shape such as a sphere, an oval sphere, a rod shape, an amorphous shape, etc. In the case of a rod shape or an amorphous shape, the length of the largest dimension may satisfy the particle diameter range.

[0051] The particle sizes of the organic particles and inorganic particles can be measured by, for example, a dynamic light scattering method, a laser diffraction method, a centrifugal sedimentation method, an FFF (Field Flow Fractionation) method, a pore electrical resistance method, or the like.

[0052] The hard coating layer included in the antiglare film may have two or more projections and recesses on the surface facing the light-transmitting substrate. The projections and recesses may be formed by aggregation of organic particles, and thus the projections and recesses may contain the organic particles. The projections and recesses may contain the entire organic particles or a part of the organic particles, for example, 50 volume % or less of the organic particles.

[0053] The ratio of two or more organic particles agglomerated to each other in the thickness direction of the hard coating layer to the total amount of the organic particles contained in the hard coating layer may be 5% or less. The "agglomeration" includes both cases where the two or more organic particles are in contact with each other or where portions of the particles overlap each other.

[0054] When the two or more organic particles are aggregated, at least two organic particles in one group consisting of two or more organic particles aggregated together may be located at different distances from one surface of the hard coating layer. By adjusting the ratio of two or more organic particles that are aggregated at different positions in the thickness direction of the hard coating layer to 5% or less, 4.5% or less, 4% or less, or 3.5% or less, the uneven shape of the hard coating layer surface can be controlled, thereby significantly improving anti-glare properties and image brightness.

[0055] The "two adjacent organic particles among two or more organic particles that are aggregated with each other" means two organic particles that are aggregated or directly contact each other in one group consisting of the two or more organic particles that are aggregated with each other.

[0056] The distance from one surface of the hard coating layer to an organic particle means the minimum distance from one surface of the hard coating layer to a point outside the organic particle, for example, the minimum distance from one surface of the hard coating layer to the surface of the organic particle.

[0057] Whether the organic particles are aggregated or whether two adjacent organic particles are located at different distances from one surface of the hard coating layer can be confirmed by visually checking the antiglare film or by using an optical device. For example, in the antiglare film, two adjacent organic particles among the two or more organic particles aggregated with each other may have foci on an optical microscope at different positions in the thickness direction based on one surface of the hard coating layer. That is, two adjacent organic particles among the two or more organic particles aggregated with each other are located at different positions in the thickness direction based on one surface of the hard coating layer, and when observing the hard coating layer while moving the focus in the thickness direction using an optical microscope, the foci at which each of the two adjacent organic particles is confirmed, that is, the positions where the individual organic particles are present, can be confirmed.

[0058] In addition, the above-mentioned aggregation ratio can be calculated by determining the number of aggregated particles and then dividing the number by the total number of particles on the same measurement surface.

[0059] As described above, two adjacent organic particles among the two or more organic particles aggregated together may be located at different distances from one surface of the hard coating layer. For example, two adjacent organic particles among the two or more organic particles aggregated together may be located with a difference in distance of 0.1 μm or more, 0.2 μm or more, 0.5 μm or more, 1 μm or more, or 2 μm or more from one surface of the hard coating layer.

[0060] The hard coating layer having the irregularities may have a ten-point mean roughness (Rz) of 0.05 μm to 0.15 μm, 0.07 μm to 0.13 μm, or 0.09 μm to 0.11 μm, and the hard coating layer may have an average spacing (Sm) of irregularities of 0.05 mm to 0.20 mm, 0.07 mm to 0.18 mm, or 0.09 mm to 0.15 mm.

[0061] The thickness of the hard coating layer may be 1 to 10 μm or 2 to 8 μm. If the thickness of the hard coating layer is less than 1 μm, it is difficult to obtain a desired hardness, and if the thickness exceeds 10 μm, the hard coating layer may curl during the process of curing the resin when it is formed.

[0062] The thickness of the hard coating layer can be determined by observing a cross section of the antiglare film using a scanning electron microscope (SEM) and measuring the thickness of the binder part of the hard coating layer.

[0063] Meanwhile, the hard coating layer is obtained by coating a photocurable coating composition containing the binder resin, organic particles, and inorganic particles on the light-transmitting substrate, and then photocuring the coated resultant.

[0064] In addition, the photocurable coating composition may further include a photoinitiator, and therefore, the photoinitiator may remain in the hard coating layer prepared from the photocurable coating composition.

[0065] The photopolymerization initiator may be any compound known to be usable in a photocurable coating composition without any particular limitation. Specifically, a benzophenone-based compound, an acetophenone-based compound, a non-imidazole-based compound, a triazine-based compound, an oxime-based compound, or a mixture of two or more of these compounds may be used.

[0066] The photopolymerization initiator may be used in an amount of 1 to 10 parts by weight, 2 to 9 parts by weight, or 3 to 8 parts by weight, based on 100 parts by weight of the binder resin. If the amount of the photopolymerization initiator is too small, uncured and residual material may be generated during the photocuring step of the photocurable coating composition. If the amount of the photopolymerization initiator is too large, unreacted initiator may remain as an impurity or the crosslinking density may be low, resulting in reduced mechanical properties of the film.

[0067] The photocurable coating composition may further include an organic solvent, non-limiting examples of which include ketones, alcohols, acetates, ethers, benzene derivatives, or a mixture of two or more thereof.

[0068] Specific examples of such organic solvents include ketones such as methyl ethyl ketone, methyl isobutyl ketone, acetylacetone, or isobutyl ketone; alcohols such as methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, or t-butanol; acetates such as ethyl acetate, i-propyl acetate, or polyethylene glycol monomethyl ether acetate; ethers such as tetrahydrofuran or propylene glycol monomethyl ether; benzene derivatives such as toluene, xylene, or aniline; or a mixture of two or more of these.

[0069] The organic solvent may be added when the components contained in the photocurable coating composition are mixed, or may be added in a state where each component is dispersed or mixed in the organic solvent and then included in the photocurable coating composition. If the content of the organic solvent in the photocurable coating composition is too low, the flowability of the photocurable coating composition may decrease, and defects such as stripes may occur in the final film. In addition, when an excessive amount of the organic solvent is added, the solid content may be low, coating and film formation may not be performed sufficiently, and the physical properties and surface characteristics of the film may be deteriorated, and defects may occur during drying and curing. For this reason, the photocurable coating composition may contain an organic solvent so that the total solid concentration of the components contained is 1 wt% to 50 wt%, or 2 wt% to 20 wt%.

[0070] Meanwhile, methods and devices commonly used for applying the photocurable coating composition may be used without any particular limitations. For example, a bar coating method such as a Meyer bar, a gravure coating method, a 2 roll reverse coating method, a vacuum slot die coating method, a 2 roll coating method, etc. may be used.

[0071] In the step of photocuring the photocurable coating composition, ultraviolet rays or visible light having a wavelength of 200 to 400 nm may be irradiated, and the exposure dose during irradiation is 100 to 4,000 mJ / cm. 2 The exposure time is not particularly limited, and can be appropriately changed depending on the exposure device, the wavelength of the irradiated light, or the exposure dose. In addition, in the step of photocuring the photocurable coating composition, nitrogen purging can be performed to apply a nitrogen atmosphere condition.

[0072] The antiglare film includes a light-transmitting substrate, which may be a transparent plastic film and may have a transmittance according to JIS K 7361 of 90% or more, 91% or more, or 92% or more.

[0073] In addition, the light-transmitting substrate may be, but is not limited to, for example, triacetyl cellulose (TAC), polyester (TPEE), polyethylene terephthalate (PET), polyimide (PI), polyamide (PA), aramid, polyethylene (PE), polyacrylate (PAR), polyethersulfone, polysulfone, diacetyl cellulose, polypropylene (PP), polyvinyl chloride, acrylic resin (PMMA), polycarbonate (PC), epoxy resin, urea resin, urethane resin, melamine resin, etc.

[0074] The light-transmitting substrate may have an in-plane retardation (Re) of 5,000 nm to 25,000 nm, or 7,000 nm to 20,000 nm, measured at a wavelength of 400 nm to 800 nm. The antiglare film including the light-transmitting substrate having such a retardation can prevent the rainbow phenomenon caused by the interference of visible light.

[0075] The in-plane retardation (Re) is defined as the thickness of the light-transmitting substrate, d, and the refractive index in the in-plane slow axis direction, n. x , the refractive index in the in-plane fast axis direction is n y When it is defined as above, it can be defined by the following formula: Re = (n x -n y )*d

[0076] The phase difference value can be defined as an absolute positive number.

[0077] The thickness of the light-transmitting substrate may be, but is not limited to, 10 to 300 μm, 30 to 250 μm, or 40 to 200 μm, taking into consideration productivity and the like.

[0078] According to another embodiment of the present invention, there is provided a polarizing plate including the antiglare film. The polarizing plate may include a polarizing film and an antiglare film formed on at least one surface of the polarizing film.

[0079] The material and manufacturing method of the polarizing film are not particularly limited, and the material and manufacturing method may be those generally known in the art. For example, the polarizing film may be a polyvinyl alcohol-based polarizing film.

[0080] A protective film may be provided between the polarizing film and the antiglare film. Examples of the protective film are not limited to, and may be at least one of a COP (cycloolefin polymer)-based film, an acrylic-based film, a TAC (triacetylcellulose)-based film, a COC (cycloolefin copolymer)-based film, a PNB (polynorbornene)-based film, and a PET (polyethylene terephtalate)-based film.

[0081] The protective film may be a substrate for forming a single coating layer when the antiglare film is manufactured. The polarizing film and the antiglare film may be laminated with an adhesive such as an aqueous adhesive or a non-aqueous adhesive.

[0082] According to another embodiment of the invention, there can be provided a display device including the antiglare film and a display panel.

[0083] Specific examples of the display device are not limited thereto, and may be, for example, a micro light emitting diode (LED) display, a mini light emitting diode (LED) display, a liquid crystal display, a plasma display device, an organic light emitting diode device, etc.

[0084] As an example, the display device may be a micro LED display including the anti-glare film and a micro LED display panel, and the anti-glare film may be located on the viewing side on the micro LED display panel.

[0085] The micro LED display panel may include a unit substrate, a pixel including a number of LED chips mounted on the unit substrate, and the size of the LED chip constituting the pixel (length of one side of the chip) may be 100 micrometers or less to achieve high resolution. Also, the display panel may have a resolution of 200 ppi or more, 300 ppi or more, or 400 ppi or more.

[0086] When a conventional anti-glare film is applied to the above-mentioned micro LED display panel, the unevenness formed on the surface of the anti-glare film acts as a lens that refracts light emitted from pixels, causing a problem of sparkling. However, the anti-glare film, in which the difference between the total haze (Ha) and the internal haze (Hi), the peak area ratio, and the transmission diffusion distribution satisfy the above-mentioned specific numerical ranges, appropriately controls the aggregation degree of the surface unevenness to prevent the problem of refracting the lens emitted from pixels, and can prevent the sparkling phenomenon and improve image clarity while maintaining excellent anti-glare properties.

[0087] As another example, the display device may be a liquid crystal display device including a pair of polarizing plates facing each other, a thin film transistor, a color filter, and a liquid crystal cell sequentially stacked between the pair of polarizing plates, and a backlight unit. In the display device including the antiglare film, the antiglare film may be disposed on one surface of the polarizing plate that is relatively far from the backlight unit among the pair of polarizing plates. Effect of the Invention

[0088] According to the present invention, there can be provided an anti-glare film that exhibits excellent anti-glare properties while preventing the sparkling phenomenon, exhibits excellent optical properties such as high light transmittance, and has excellent physical properties such as scratch resistance, high strength, and stain resistance, as well as a polarizing plate and a display device including the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0089] The present invention will be described in more detail with reference to the following examples, however, the following examples are merely illustrative of the present invention and are not intended to limit the scope of the present invention.

[0090] [Production Example 1: Production of coating solution for forming hard coating layer] 50 g of pentaerythritol triacrylate, 50 g of MU9800 (9-functional urethane acrylate oligomer, manufactured by MIWON, weight average molecular weight: 3500 g / mol, acrylate group equivalent: 389 g / mol), 7 g of D1173 (manufactured by Ciba) as an initiator, 100 g of methyl isobutyl ketone as a solvent, 21 g of MA-ST (nanosilica particles, manufactured by Nissan Chemical, particle size: 10 to 15 nm, 30% in methanol), and 12 g of PS-a (polystyrene spherical particles, particle size 3.5 μm, refractive index: 1.595) were mixed to produce a hard coating layer forming composition of Production Example 1.

[0091] At this time, the particle size of the particles was measured by a dynamic light scattering method.

[0092] [Production Example 2: Production of coating solution for forming hard coating layer] A composition for forming a hard coating layer of Preparation Example 2 was prepared by mixing 30 g of pentaerythritol triacrylate, 70 g of MU9800, 7 g of D1173 as an initiator, 100 g of methyl isobutyl ketone as a solvent, 17 g of MA-ST, and 12 g of PS-a.

[0093] [Production Example 3: Production of coating solution for forming hard coating layer] 50g of pentaerythritol triacrylate, 50g of MU9800, 7g of D1173 as an initiator, 100g of methyl isobutyl ketone as a solvent, 20g of PMA-ST (nanosilica particles, manufacturer: Nissan Chemical, particle size: 10-15nm, 30% in propylene glycol monomethyl ether acetate), 8g of PS-a, and 3g of PS-PMMA-a (polystyrene-polymethyl methacrylate copolymer spherical particles, particle size 3.5μm, refractive index: 1.555) were mixed to prepare a composition for forming a hard coating layer of Preparation Example 3.

[0094] [Production Example 4: Production of coating solution for forming hard coating layer] A hard coating layer-forming composition of Preparation Example 4 was prepared by mixing 50 g of pentaerythritol triacrylate, 50 g of MU9800, 7 g of D1173 as an initiator, 100 g of methyl isobutyl ketone as a solvent, 1.2 g of MA-ST, and 5 g of PS-PMMA-b (polystyrene-polymethyl methacrylate copolymer spherical particles, particle size 2 μm, refractive index: 1.555).

[0095] [Production Example 5: Production of coating solution for forming hard coating layer] A composition for forming a hard coating layer of Preparation Example 5 was prepared by mixing 100 g of pentaerythritol triacrylate, 7 g of D1173 as an initiator, 100 g of methyl isobutyl ketone as a solvent, 27 g of MA-ST, and 12 g of PS-a.

[0096] [Production Example 6: Production of coating solution for forming hard coating layer] 100 g of EB1290 (hexafunctional urethane acrylate oligomer, manufacturer: SK Cytec, weight average molecular weight: 1,000 g / mol, acrylate group equivalent: 167 g / mol), 7 g of D1173 as an initiator, 100 g of methyl isobutyl ketone as a solvent, 23 g of MA-ST, and 12 g of PS-a were mixed to prepare a composition for forming a hard coating layer of Preparation Example 6.

[0097] [Production Example 7: Production of coating solution for forming hard coating layer] 50 g of pentaerythritol triacrylate, 50 g of EB1290, 7 g of D1173 as an initiator, 50 g of methyl isobutyl ketone as a solvent, 50 g of toluene, 8 g of PS-b (polystyrene spherical particles, particle size 2 μm, refractive index: 1.595), and 8 g of SS-50B (surface-treated hydrophobic silica particles, manufacturer: Tosoh, particle size 2 μm) were mixed to produce a composition for forming a hard coating layer of Production Example 7.

[0098] [Production Example 8: Production of coating solution for forming hard coating layer] A hard coating layer-forming composition of Preparation Example 8 was prepared by mixing 50 g of pentaerythritol triacrylate, 50 g of EB1290, 7 g of D1173 as an initiator, 50 g of methyl isobutyl ketone as a solvent, 50 g of toluene, and 12 g of SS-50B.

[0099] [Examples and Comparative Examples: Production of Antiglare Film] The compositions for forming hard coating layers of Production Examples 1 to 8 were coated on a light-transmitting substrate, triacetyl cellulose (TAC, thickness 60 μm), using a #10 Meyer bar as shown in Table 1 below, and dried at 90° C. for 1 minute. 2 The antiglare film was manufactured by irradiating the film with ultraviolet rays of 1000 nm to form a hard coating layer. The thickness of the hard coating layer is shown in Table 1 below.

[0100] [Table 1]

[0101] <Experimental Example> [1. Peak area (I B / I A ) ratio The hard coating layer of the antiglare film obtained in each of the Examples and Comparative Examples was subjected to IR measurement using a Cary660 (Agilent) device. -1 ~1745cm -1 The peak area between the regions (I A ) for 1500 cm -1 ~1570cm -1 The peak area between the regions (I B ) ratio (I B / I A ) was calculated, and the results are shown in Table 2 below.

[0102] At this time, the IR measurement conditions were as follows: -ATR:PIKE Technologies 025-2018 Miracle Znse perf crystal plate -Measurement wavelength: 400~4000nm -Measurement temperature: 25℃

[0103] [2. Measurement of transmittance and haze] A 4cm x 4cm test piece was prepared from each of the antiglare films obtained in the examples and comparative examples, and was measured three times with a haze meter (HM-150, A light source, MURAKAMI Co., Ltd.) to calculate the average value, which was calculated as the overall haze value. At this time, the light transmittance and the overall haze were measured simultaneously, and the light transmittance was measured according to JIS K 7361 and the haze was measured according to JIS K 7136.

[0104] When measuring the internal haze, an adhesive film with an overall haze of 0 was attached to the hard coating layer to smooth out the surface irregularities, and the internal haze was measured in the same manner as the overall haze.

[0105] [3. Transmission diffusion distribution] The antiglare films obtained in the examples and comparative examples were set in a goniometer (GC5000L, Nippon Denshoku Industries Co., Ltd.), and light was irradiated in the normal direction of the light-transmitting substrate of the antiglare film, and the intensity of the light transmitted through the hard coating layer was measured. At this time, the intensity of the light transmitted in the linear direction of the hard coating layer was set as the transmitted intensity (A), and the intensity of the light transmitted at +1° or -1° based on the normal line of the hard coating layer was set as the transmitted diffusion intensity (B), which was substituted into the following formula 1 to calculate the transmitted diffusion distribution, and the results are shown in Table 2 below. [Formula 1] Transmission diffusion distribution = (B / A) x 100

[0106] [4. Measurement of specular reflection intensity ratio] A flat black adhesive-coated polyethylene terephthalate film without unevenness or warping was attached to one side of a light-transmitting substrate so as to face the hard coating layer of the anti-glare film obtained in each of the Examples and Comparative Examples to prepare a specimen. The specimen was then placed in a goniometer (GC5000L, Nippon Denshoku Industries Co., Ltd.) and light was irradiated at an angle of 45° from the normal line of the surface to the hard coating layer surface of the specimen. After the light was irradiated to the hard coating layer surface, the reflection intensity (C) was measured at an incident angle of 45°, which corresponds to regular reflection.

[0107] In addition, in the examples and comparative examples, a polyethylene terephthalate film coated with a flat black adhesive without unevenness or warping was attached to one side of the light-transmitting substrate on which the hard coating layer was not formed to prepare a test piece, and the reflection intensity (D) was measured in the same manner as in measuring the reflection intensity (C).

[0108] The measured reflection intensities C and D were substituted into the following formula 2 to calculate the regular reflection intensity ratio, and the results are shown in Table 2 below. [Formula 2] Specular reflection intensity ratio=(C / D)×100

[0109] [5. Check for sparkling] A sample of 12cm x 12cm was prepared for the anti-glare film obtained in each of the Examples and Comparative Examples, and attached to a slide glass with a transparent adhesive film (OCA). Then, the sample was placed on a panel with a resolution of 400ppi with the hard coating surface facing up. At this time, tape may be attached to the inclined surface to prevent the film from lifting. Then, the panel was driven so that a white screen was visible, and the presence or absence of sparkling was confirmed within an area of ​​10cm x 10cm of the sample. The evaluation criteria are as described below, and the results are shown in Table 2 below. Good: No sparkle of light Defective: Sparkling light

[0110] [6. Evaluation of anti-glare properties] A polyethylene terephthalate film coated with a black adhesive, which was flat and free of unevenness or warping, was attached to one side of a light-transmitting substrate so as to face the hard coating layer of the anti-glare film obtained in each of the Examples and Comparative Examples to prepare a test specimen. Then, using a fluorescent lamp having two rows of lamps as a light source, the field of view was observed from the direction of regular reflection of each anti-glare film, and the visual sensation was measured by classifying the image of the image reflected by the fluorescent lamp. The visual sensation evaluation criteria are as described below, and the results are shown in Table 2 below. Good: No lamp image observed Poor: Lamp image is clearly visible

[0111] [Table 2]

[0112] According to Table 2, the anti-glare films of Examples 1 to 3 have an internal haze of 10 or more, a difference between the total haze and the internal haze of 5 to 15%, a peak intensity ratio of 0.1 to 0.6, and a transmission diffusion distribution of more than 1% and less than 10%, and therefore exhibit excellent anti-glare properties without causing sparkling. On the other hand, it was confirmed that Comparative Examples 1 to 5 have problems such as sparkling and poor anti-glare properties.

Claims

1. A laminate including: a light-transmitting substrate; and a hard coating layer including a binder resin and organic and inorganic particles dispersed in the binder resin; The laminate has a difference (Ha-Hi) between the overall haze (Ha) and the internal haze (Hi) of 5 to 15%, The IR spectrum of the laminate shows 1690 cm -1 ~1745cm -1 The peak area (I A ) for 1500 cm -1 ~1570cm -1 The peak area (I B ) ratio (I B / I A ) is 0.1 to 0.6, The laminate has a transmittance diffusion distribution according to the following formula 1 of more than 1% and less than 10%, The laminate is an antiglare film having a regular reflection intensity ratio of more than 1% and less than 10% as represented by the following formula 2: [Formula 1] Transmission diffusion distribution=(B / A)×100 A is the transmission intensity measured by irradiating the light-transmitting substrate with light in the normal direction and then transmitting the hard coating layer in the normal direction, B is the transmission diffusion intensity measured by irradiating light in the normal direction of the light-transmitting substrate and then measuring the light transmitted at +1° or −1° with respect to the normal of the hard coating layer. [Formula 2] Specular reflection intensity ratio = (C / D) x 100 In the above formula 2, C is the reflection intensity measured at an incidence angle of 45°, which corresponds to regular reflection, after irradiating the hard coating layer with light at an incidence angle of 45°; D is the reflection intensity measured at an incidence angle of 45°, which corresponds to specular reflection, after irradiating the light-transmitting substrate with light at an incidence angle of 45°.

2. The antiglare film according to claim 1, wherein the laminate has an overall haze of 20% to 50% and an internal haze of 10% to 40%.

3. 3. The antiglare film according to claim 1, wherein the binder resin comprises a polyfunctional (meth)acrylate monomer and a urethane (meth)acrylate oligomer in a weight ratio of 3:7 to 7:

3.

4. The antiglare film according to any one of claims 1 to 3, wherein the organic particles have a particle size of 1 µm to 10 µm.

5. The antiglare film according to any one of claims 1 to 4, wherein the inorganic particles have a particle size of 1 nm to 500 nm.

6. The antiglare film according to any one of claims 1 to 5, wherein the weight ratio of the organic particles to the inorganic particles is 1:0.2 to 1.

5.

7. The antiglare film according to any one of claims 1 to 6, wherein the hard coating layer comprises: a binder resin containing a multifunctional (meth)acrylate monomer and a urethane (meth)acrylate oligomer in a weight ratio of 3:7 to 7:3; and organic particles having a particle size of 1 μm to 10 μm and inorganic particles having a particle size of 1 nm to 500 nm dispersed in the binder resin.

8. The antiglare film according to any one of claims 1 to 7, wherein two or more projections and recesses containing the organic particles are formed on a surface of the hard coating layer.

9. 9. The antiglare film according to claim 1, wherein a ratio of two or more organic fine particles agglomerated to each other in a thickness direction of the hard coating layer is 5% or less in the total amount of the organic particles.

10. The antiglare film according to any one of claims 1 to 9, wherein the hard coating layer has a ten-point average roughness (Rz) of 0.05 µm to 0.15 µm and an average spacing (Sm) of irregularities of 0.05 mm to 0.20 mm.

11. The antiglare film according to any one of claims 1 to 10, wherein the light-transmitting substrate has an in-plane retardation (Re) of 5000 to 25000 nm measured at a wavelength of 400 nm to 800 nm.

12. A polarizing plate comprising the antiglare film according to any one of claims 1 to 11.

13. A display device comprising the antiglare film according to any one of claims 1 to 11 and a display panel.

14. 14. The display device of claim 13, wherein the display panel has a resolution of 200 ppi or greater.

Citation Information

Patent Citations

  • Light diffusion film, polarizer, image display device, and manufacturing method of light diffusion film

    JP2012098425A

  • Antiglare film, polarizing plate, and image display device

    JP2014016602A

  • Antiglare film and method for producing the same

    KR1020100073252A

  • Antiglare film with various inner and outer haze

    US20120092773A1

  • Antiglare film, polarizer and image display device

    US20130279155A1